A SYSTEMATIC LITERATURE REVIEW OF GREEN BUILDING IMPLEMENTATION FOR IMPROVING ENERGY EFFICIENCY AND ENVIRONMENTAL SUSTAINABILITY - Meisy Ariani; Septya Salsalbilla; M. Heri Zulfikar (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
The application of green building concepts is not only intended to minimize carbon emissions but also to enhance the well being and comfort of building occupants through healthier spatial designs. Although this approach offers multiple advantages, its adoption still encounters several challenges most notably, the substantial initial investment costs and the absence of comprehensive regulatory frameworks, particularly in developing nations. This study aims to evaluate how effectively the sustainable building concept contributes to improving energy performance, conserving natural resources, and mitigating negative environmental impacts. A qualitative descriptive method was employed, using a literature study approach. The research encompassed a population of scientific works discussing the implementation of green buildings both within Indonesia and internationally. Samples were selected purposively, focusing on relevance and the recency of the materials. Data were gathered from various secondary sources such as academic journals, textbooks, and institutional reports, and analyzed through thematic synthesis and interpretative techniques to uncover implementation trends, barriers, and sustainability strategies. The findings reveal that applying green building principles can increase energy efficiency by approximately 20–30%, optimize the use of eco friendly materials, and foster a healthier, more comfortable built environment.